Evaluation of the performance of damage insurance companies in Algeria after the restructuring process in accordance with Law 06-04: CAAT model - salem, radia (Journal of Research in Finance and Accounting, 2023)
This study aims to identify the results of the restructuring process on the performance of damage insurance companies in Algeria, This is in implementation of the reforms introduced by Law 04-06, which constituted a basic requirement for the development of life insurance services, Thus, we analyzed the performance of CAAT as a model for the study, By estimating a set of indicators used to evaluate performance during the period (2006-2020). The study concluded many results: The restructuring process did not achieve the expected results, It only resulted in an increase in the number of life insurance companies, Without having an impact on the performance of damage insurance companies, where This branch’s till occupies the dominant position in the Algerian insurance market before and after the restructuring.